Cupping Therapy Drains the Extra Lipids in Migraine Headache Patients - Soomro, Zeba Hussain; Aslam Channa, Naseem; Shaikh, Marvi; Ahmed, Zahoor; Awan, Amna Yasin; Solangi, Shazia Parveen (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine how wet cupping affects the clinical and laboratory parameters of individuals with migraine headaches. METHODOLOGY: This cross-sectional study was conducted at the Department of Neurology, Dr Ruth K M Pfau Hospital, Karachi and Hamdard University in collaboration with the Institute of Biochemistry, University of Sindh, Jamshoro, from January 2021 to December 2023. A total of 102 migraine headache patients aged 15 to 70 years, including 32 males and 70 females, with evidence of migraine headache and normal EEG, who confirmed the migraine, participated in the study after providing written informed consent. Patients with abnormal EEG tests younger than 15 were excluded from the study. The patients underwent wet cupping; 5ml intravenous blood samples were collected before the procedure, 5ml from the cups, and 5ml intravenous blood was collected after one week of cupping therapy. The spectroscopic method analyzed all the samples for serum lipid profile. Data analysis was performed using SPSS Version 26, with a significance level set as p<0.05 at a 95% confidence interval. RESULTS: Most migraine patients were female. The wet cupping samples exhibited significant increases p<0.05 in lipid and liver profiles compared to pre-cupping samples, although they remained within normal ranges. No significant variations were observed in gender-specific comparisons for serum lipids. Additionally, age-wise comparisons revealed no significant differences among migraine patients of various age groups in pre-cupping and cupping samples. CONCLUSION: Wet cupping therapy drains the extra serum lipids and reduces migraine headaches.